Students' Science Literacy Exploration in Process Oriented Inquiry Learning (POGIL) Based Learning - Ginting, Fajrul Wahdi; Sakdiah, Halimatus; Unaida, Ratna (PT FORMOSA CENDEKIA GLOBAL, 2024)
Science literacy is important because it allows individuals to understand, analyze, and interpret scientific information that is relevant to everyday life. The POGIL learning model, which focuses on structured inquiry activities, is expected to improve students' science literacy by integrating process-based and collaborative approaches. The purpose of this study was to see the effect of Process Oriented Guided Inquiry Learning (POGIL) on science literacy. This study used a quasi-experimental method, with a research design using one group pretest-posttest design. The sample was drawn by total sampling so that it used 30 students. The application of POGIL activated discussion and collaboration in the learning process. The results of the Wilcoxon test obtained a sig of 0.000 and it was concluded that there was an effect of POGIL on science literacy. The highest science literacy indicator was the Identifying Valid Scientific Opinions indicator with a percentage value of 98.33%. researchers had difficulty in directing students to collaborate, but this could be overcome by creating heterogeneous groups.